STUDI KOMPARATIF SANKSI DAN PERTANGGUNGJAWABAN TERHADAP TINDAK PIDANA YANG DILAKUKAN ANAK DALAM PERSPEKTIF HUKUM POSITIF DI INDONESIA DAN HUKUM ISLAM - Nasution, Muhammad Karim (KODIFIKASI, 2020)
Current violations of the law are very unfavorable for the community. Due to certain factors, the interesting thing is not only the society that has grown up, even the children under the age of it are not uncommon for us to find children as perpetrators of criminal activity.The formulation of the problem of this research is about giving penalties for crimes committed by children in the perspective of positive Indonesian law and Islamic law, and how responsibility for criminal acts committed by children in the positive perspective of Indonesian law and Islamic law.The purpose of this research is to study the implementing regulations for criminal acts committed by children in the perspective of positive law in Indonesia and Islamic law and to understand the responsibility of criminal acts committed by children in the perspective of positive law in Indonesia and Islamic law..From the results of research and discussion conclusions obtained from the Accountability of child punishment according to the Criminal Law Act regulated in Articles 45, 46 and 47. According to Article 45, 46 and 47 children whose age has not reached 16 (sixteen) years, cannot be sentenced because Article 45. And if a child is sentenced then the sentence received is one third of the sanction of an adult. Meanwhile, according to Islamic law, children must take responsibility for their actions if they have to do baligh. A child who has not yet begun baligh is not obliged to take responsibility for his actions